Good Vibrations Brian Wilson and the Beach Boys in Critical Perspective - Lambert, Philip (University of Michigan Press, 2016)
"Good Vibrations brings together scholars with a variety of expertise, from music to cultural studies to literature, to assess the full extent of the contributions to popular culture and popular music of one the most successful and influential pop bands of the twentieth century. The book covers the full fifty-year history of the Beach Boys' music, from essays on some of the group's best-known music-such as their hit single "Good Vibrations" -to their mythical unfinished masterpiece, Smile. Throughout, the book places special focus on the individual whose creative vision brought the whole enterprise to life, Brian Wilson, advancing our understanding of his gifts as a songwriter, arranger, and producer. The book joins a growing body of literature on the popular music of the 1960s, in general, and on Brian Wilson and the Beach Boys in particular. But Good Vibrations extends the investigation further and deeper than it has gone before, not only offering new understanding and insights into individual songs and albums, but also providing close examination of compositional techniques and reflections on the group's place in American popular culture."